Comparative analysis of conventional and low-GWP refrigerants with ionic liquid used for compression-assisted absorption cooling cycles. (25th May 2020) - Wu, Wei; Leung, Michael; Ding, Zhixiong; Huang, Hongyu; Bai, Yu; Deng, Lisheng
Highlights: Low-GWP refrigerants are studied for compression-assisted single-effect absorption cooling cycles. Different hydrofluorocarbons and hydrofluoroolefins are paired with ionic liquid as alternative working fluids. Difluoromethane has the highest COPs while 2, 3, 3, 3-tetrafluoropropene has the lowest in most conditions. Compression ratios are optimized to be 1.9–3.4 with the maximum COPs of 0.546–0.663. Low-pressure compression-assisted absorption cooling cycle features high efficiency and low discharge temperature. Abstract: To address the problems of conventional absorption technologies, various working pairs consisting of low-global-warming-potential hydrofluorocarbons/hydrofluoroolefins and ionic liquid were numerically investigated for two compression-assisted absorption cooling cycles driven by heat sources at lower temperatures. The property prediction model and thermodynamic performance model were established and verified. The performance improvements were evaluated and the compression ratio was optimized. With the compression-assisted absorption cycle, the coefficient of performance (COP) was enhanced from 0.191–0.463 to 0.366–0.670, while the minimum generation temperature was reduced by about 20 °C, reaching 45 °C. For both basic and compression-assisted absorption cycles, difluoromethane yielded the highest COP, followed by fluoroethane and 1, 1-difluoroethane with slightly lower COPs; 2, 3, 3, 3-tetrafluoropropene performed the worst in most conditions; 1, 1, 1, 2-tetrafluoroethane performed worse than trans -1, 3, 3, 3-tetrafluoropropene using the basic cycle but outperformed trans -1, 3, 3, 3-tetrafluoropropene using the compression-assisted absorption cycle. The thermal COP varies similarly to but higher than the COP, while the mechanical COPs are much higher for all the working pairs, reaching 11–14 (R152a showing the highest) with a CR of 1.5. The mechanical COP decreases dramatically with the compression ratio. For the low-pressure compression-assisted absorption cycle with a generation temperature of 70 °C, the optimal compression ratios were 1.9–3.4 with the maximum COPs of 0.546–0.663 and were 1.3–2.2 with the maximum exergy COPs of 0.192–0.289. The low-pressure compression-assisted absorption cycle was better than the high-pressure compression-assisted absorption cycle due to the higher cycle efficiency and lower compressor discharge temperature. This study provides suggestions on the selection of compression-assisted absorption cycles, working pairs and optimal parameters for renewable/waste cooling.